Evaluación y diseño de tecnologías basadas en la pirólisis a pequeña escala, como alternativa para el aprovechamiento y disposición final de residuos plásticos en zonas rurales del país. (2022)
Plastic waste in recent years has generated a worldwide problem due to its low level of decomposition in the environment, the consequence that plastics generate is the same disintegration of their particles and the bioaccumulation that they produce, the burning of these plastics in areas of difficult access as well as in rural areas, it causes the release of greenhouse gases as well as toxic gases for humans and animal species that live near these places is of high risk and environmental impact. Processes have been proposed for the use of plastic waste, among which is chemical recycling, which includes depolymerization, gasification and pyrolysis, mechanical recycling and energy use.